Ductile to Brittle Transition of Short Carbon Fiber-Reinforced Polypropylene Composites - Harri Junaedi; Essam Albahkali; Muneer Baig; Abdulsattar Dawood; Abdulhakim Almajid (Advances in Polymer Technology)
In this work, the ductile to brittle transition behavior of short carbon fiber (SCF)-reinforced polypropylene (PP) composite is studied. Initially, the SCF-reinforced PP composites with a varying composition of SCF in the range of 0–40 wt% loading were first melt-mixed in a twin-screw extruder and later injection-molded to produce the testing samples. The experimental results indicate that with an increase in SCF loading, an increase in the tensile modulus and strength was observed along with a rapid decrease in the values of strain at break. A sudden decrease in strain at break was observed in composites in the range of 10–15 wt% SCF. To further study the sudden decrease in strain at break, an investigation was performed on composites that contained 10–15 wt% of SCF loading, starting from 10 wt% with a 1% increment to 15 wt% of SCF. The results of this study show that a decrease in strain at break was not linear; on the contrary, it was accompanied by a ductile to brittle transition, which specifically occurred in the range of 12–13 wt% of SCF loading and then continued to decrease with an increase in SCF loading.